Association of the Composite dietary antioxidant index with all-cause and cardiovascular mortality: A prospective cohort study - Wang, Lei; Yi, Zhong (Frontiers in Cardiovascular Medicine, 2022)
Background According to epidemiological and experimental data, high individual dietary antioxidant intake is correlated with reduced cancer risk. The correlations between combined dietary antioxidants and the risk of all-cause and cardiovascular mortality remain unclear. Consequently, this study focused on evaluating the correlation between the food-derived Composite Dietary Antioxidant Index (CDAI) and all-cause and cardiovascular mortality. Methods Two years of data collected from participants aged ≥20 years were included in this prospective cohort study, which was obtained from the US National Health and Nutrition Examination Survey (NHANES) from 1999 to 2018. The US NHANES adopted a complicated, multistage probability sampling method to collect health data representing the US population. Data collection was done through in-person interviews, virtual physical examinations, and laboratory tests. Mortality-related follow-up statistics from the start of the survey to 31 December 2019 were available. The shape of the correlation between CDAI and all-cause and cardiovascular mortality was inspected using a restricted cubic spline model. For CDAI and all-cause and cardiovascular mortality, the univariate- and multivariate-adjusted Cox proportional hazard models were estimated and presented as regression coefficients and 95% confidence intervals. Results In total, 44,031 NHANES participants represented 339.4 million noninstitutionalized residents of the US (age, 47.2 ± 16.9 years; 52.5% women, 70.2% non-Hispanic whites, 10.8% non-Hispanic black people, and 7.5% Mexican Americans). In the 118-month follow-up, 9,249 deaths were reported, including 2,406 deaths resulting from heart disease and 519 deaths due to cerebrovascular disease. In the restricted cubic spline regression models, a linear relationship between CDAI and all-cause mortality was present. The weighted multivariate hazard ratios for all-cause mortality were computed to be 0.97 (0.87-1.07) for Q2, 0.88 (0.81-0.96) for Q3, and 0.90 (0.80-1.00) for Q4 (P for trend = 0.009) upon comparison with the lowest quartile of CDAI, and an identical trend was observed for cardiovascular mortality. Conclusion A high CDAI was linked to decreased all-cause and cardiovascular mortality risk. The intake of an antioxidant-rich diet significantly prevents cardiovascular mortality. To shed more light on these outcomes, more itemized investigations such as randomized control trials are required.